2016
DOI: 10.1016/j.eats.2016.02.002
|View full text |Cite
|
Sign up to set email alerts
|

Proximal Rectus Femoris Avulsion Repair

Abstract: Proximal rectus femoris tendon avulsions are rare and occur mostly in male athletes. Currently, the standard of care for complete tendinous avulsions of the direct arm of the rectus femoris is nonoperative treatment. However, surgical repair may be considered in high-level athletes who have a high demand for repetitive hip flexion performed in an explosive manner or in patients in whom nonoperative treatment has failed. The purpose of this technical note is to describe the method for surgical repair of the pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
50
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(54 citation statements)
references
References 13 publications
3
50
0
1
Order By: Relevance
“…According to our experience, MRI can detect patients who could benefit from surgery by showing enlarged diffuse hematoma at the original insertion of the PRF as a sign of a ruptured fascia as well as a retracted tendon stump. Dean et al 2 postulated that nonoperative treatment leads to good results if the PRF tear has minimal retraction, with which we also agree. When PRF tears have minimal retraction and the fascia over the ruptured tendon is intact, nonoperative treatment leads to good results.…”
Section: Discussionsupporting
confidence: 87%
See 3 more Smart Citations
“…According to our experience, MRI can detect patients who could benefit from surgery by showing enlarged diffuse hematoma at the original insertion of the PRF as a sign of a ruptured fascia as well as a retracted tendon stump. Dean et al 2 postulated that nonoperative treatment leads to good results if the PRF tear has minimal retraction, with which we also agree. When PRF tears have minimal retraction and the fascia over the ruptured tendon is intact, nonoperative treatment leads to good results.…”
Section: Discussionsupporting
confidence: 87%
“…These indications were high-demand patients (high-level athletes) and failure of nonoperative treatment (pain and weakness for over 3 months), whereas contraindications were described as nondisplaced avulsions, tears without retraction, and low-demand patients in whom chronic tears do not interfere with normal daily function. 2 These indications are also in line with our practice.…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…In the present study, surgical repair of proximal rectus femoris avulsion injuries enabled return to preinjury level of sporting function at 15.8 ± 2.2 weeks, which is more favorable than reports from existing studies using smaller sample sizes of patients with similar preinjury levels of activity. 11,15,20,23,34,37 Irmola et al 20 followed 4 professional soccer players and 1 national-level hurdler who underwent surgical repair of complete proximal rectus femoris avulsion injuries and reported that the median time for return to sporting activity was 9 months (range, 5-10 months). However, time from injury to surgical intervention was 18 to 102 days, which may have adversely affected postoperative rehabilitation time.…”
Section: Discussionmentioning
confidence: 99%